Improvements in the structural and optical properties of in2o3 nanostructure by in-situ thermal annealing / Azianty Saroni ... [et al.] - Saroni, Azianty; Abdul Rahman, Saadah; Tong Goh, Boon; Alizadeh, Mahdi (Universiti Teknologi MARA Cawangan Pahang, 2020)
In2O3/W2N nanocomposites have been successfully grown by a single step deposition technique. The nanostructures were characterized by field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), Ultraviolet-Visible spectroscopy (UV-Vis), and X-ray photoelectron spectroscopy (XPS). The structure deformation of In2O3 nanostructure by an in-situ thermal annealing under ambient nitrogen plasma treatment was investigated. The In2O3 nanostructure demonstrated a decreasing in particle size when it was exposed to in- situ thermal annealing by a hot-filament at temperature of 1700 ºC. The in-situ thermal annealing enhances the surface mobility of the N adatoms to reach the nucleation sites to form crystalline W2N. The formation of chemical composition of In2O3 and W2N nanostructures presented in the material were analyzed by XPS spectra. The crystallinities of these nanostructures were revealed by XRD patterns showing the cubic, hexagonal and cubic of In2O3 and W2N structures respectively. The decreasing of the optical energy gap, Eg from 2.89 to 1.69 eV which is in the visible region could be attributed to the incorporation of nitrogen into the In2O3 and the formation of In2O3/W2N nanocomposites.